Ketimpangan Relasi Kuasa Dalam Kasus Kekerasan Seksual di Perguruan Tinggi - Saputra, Muh Iksan; Norfazilah, Norfazilah; Ramadhani, Anugrah; Marlina, Andi (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2024)
This research aims to identify the role of institutional hierarchies, social norms, and power imbalances in facilitating sexual violence in higher education and provide a solid foundation for the development of effective prevention and response strategies. The research involved analyzing institutional policies and practices with the aim of reducing unequal power relations and preventing sexual violence in academic settings. The research method involved an in-depth literature review using various reference sources such as books, scholarly journals, experts’ legal views, and relevant legislation. The main focus of this research is to understand the causal factors of sexual violence in higher education and formulate effective prevention strategies. Sexual violence in higher education has a profound impact physically, psychologically, emotionally, and socially. This research highlights unequal power relationships, the need for identification of causal factors, strict policy implementation, collaboration, and awareness through education to create a safer and fairer environment. Students’ lack of understanding of sexual harassment can hinder critical action, and the “iceberg” phenomenon emphasizes the importance of raising awareness of the issue. With a deep understanding of power dynamics, prevention strategies can shape a safer and more equitable academic environment. Unequal power relations play a major role in amplifying sexual violence. ___ Referensi Buku dengan penulis: Syam, N. (2010). Agama Pelacur; Dramaturgi Transendental. Yogyakarta: LKIS Pelangi Aksara. Artikel jurnal: Alpian, R. (2022). Perlindungan Hukum Pidana terhadap Tindak Kekerasan Seksual di Dalam Institusi Perguruan Tinggi. Lex Renaissance, 7(1), 69-83. Elindawati, R. (2021). Perspektif Feminis Dalam Kasus Perempuan sebagai Korban Kekerasan Seksual di Perguruan Tinggi. AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 15(2), 181-193. Fitri, A., Haekal, M., Almukarramah, A., & Sari, F. M. (2022). Sexual Violence in Universities in Indonesia: Between Student Negation and Resistance. Kafaah: Journal of Gender Studies, 12(2), 106-122. Fitriyanti, E., & Suharyati, H. (2023). Pelecehan Seksual Fisik di Perguruan Tinggi: Tinjauan terhadap Faktor Penyebab, Dampak, dan Strategi Kebijakan sebagai Upaya Pencegahan. Sosio e-Kons, 15(2), 178-195. Irianto, S. (2021). Power Relations and Sexual Violence on the Campus. Jurnal Perempuan, 26(2), 135-141. Israpil, I. (2017). Budaya Patriarki dan Kekerasan terhadap Perempuan (Sejarah dan Perkembangannya). Pusaka, 5(2), 141-150. Miele, C., Maquigneau, A., Joyal, C. C., Bertsch, I., Gangi, O., Gonthier, H., ... & Lacambre, M. (2023). International Guidelines for the Prevention of Sexual Violence: A Systematic Review and Perspective of WHO, UN Women, UNESCO, and UNICEF's PUBLICATIONS. Child Abuse & Neglect, 146, 106497. Miraviori, A. D. S. (2018). Ruang yang Dibenturkan: Membaca Absurditas Tiga Naskah Drama Afrizal Malna. Jurnal Seni Nasional Cikini, 3(3), 23-34. Purwanda, S. (2020). The Existence of the Right to Books for Frontier, Outermost and Disadvantaged Regions as Part of the Right to Enjoy Education. JL Pol'y & Globalization, 95, 42. Purwanda, S., Bakhtiar, H. S., Miqat, N., Nur, R., & Patila, M. (2022). Formal Procedure Versus Victim's Interest: Antinomy of Handling Sexual Violence Cases in East Luwu. Jurnal Hukum Volkgeist, 6(2), 116-122. Purwanda, S., & Dewi, M. N. K. (2020). The Effects of Monism and Pluralism on Legal Development of a Nation. Amsir Law Journal, 2(1), 21-26. Puspytasari, H. H. (2022). Pemahaman Mahasiswa Terhadap Kekerasan Seksual di Perguruan Tinggi. Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 28(1), 123-132. Rakhmawati, D., Maulida, D., & Yuliejantiningsih, Y. (2022). Pembanjiran Informasi, Asertivitas Seksual dan Kekerasan Seksual di Perguruan Tinggi. Indonesian Journal of Guidance and Counseling: Theory and Application, 11(2), 75-82. Rohima, S., Saleh, S., & Pertiwi, R. (2023). Sosialisasi Pencegahan dan Penanganan Kekerasan Seksual Pada Perguruan Tinggi di Kota Palembang. Sricommerce: Journal of Sriwijaya Community Services, 4(1), 49-60. Rusyidi, B., Bintari, A., & Wibowo, H. (2019). Pengalaman dan Pengetahuan tentang Pelecehan Seksual: Studi Awal di Kalangan Mahasiswa Perguruan Tinggi (Experience and Knowledge on Sexual Harassment: A Preliminary Study Among Indonesian University Students). Share: Social Work Journal, 9(1), 75-85. Saripudin, U., Nurlaeli, S., & Fatriany, F. (2022). Pertanggungjawaban Pidana Pelaku Kekerasan Seksual di Lingkungan Perguruan Tinggi berdasarkan UU TPKS. VARIA HUKUM, 4(2), 65-79. Sumintak, S., & Idi, A. (2022). Analisis Relasi Kuasa Michel Foucault: Studi Kasus Fenomena Kekerasan Seksual di Perguruan Tinggi. Jurnal Intelektualita: Keislaman, Sosial dan Sains, 11(1), 55-61. Supriansyah, S. (2023). Konstruksi Remaja Perempuan Urban di Film Indonesia Kontemporer: Antara Gender, Seksualitas, dan Agama. Muadalah, 11(1), 27-42. Umar, T. M. (2005). Propaganda Feminisme dan Perubahan Sosial. Mediator: Jurnal Komunikasi, 6(2), 205-214. Van der Bruggen, M., & Grubb, A. (2014). A Review of the Literature Relating to Rape Victim Blaming: An Analysis of the Impact of Observer and Victim Characteristics on Attribution of Blame in Rape Cases. Aggression and Violent Behavior, 19(5), 523-531. Zahir, F. I., & Saputra, S. A. (2024). Upaya Pencegahan Tindak Kekerasan Seksual pada Perempuan Berbasis Buku Panduan. Jurnal Ilmu Pendidikan dan Psikologi, 1(2), 50-58. World Wide Web: Ahdiat, A. (2023). Kampus, Lingkungan Pendidikan dengan Kekerasan Seksual Terbanyak. Diakses dari laman: https://databoks.katadata.co.id/datapublish/2023/12/20/kampus-lingkungan-pendidikan-dengan-kekerasan-seksual-terbanyak Ajie, M. T., & Romanti, R. (2021). Mendikbudristek: Ada Darurat Kekerasan Seksual di Lingkungan Perguruan Tinggi! Diakses dari laman: https://itjen.kemdikbud.go.id/web/mendikbudristek-ada-darurat-kekerasan-seksual-di-lingkungan-perguruan-tinggi/ Departemen Riset Statista. (2023). Persepsi tentang Alasan Terjadinya Kekerasan Seksual di Indonesia Tahun 2020. Diakses dari laman: https://www-statista-com.translate.goog/statistics/1250314/indonesia-perception-on-causes-of-sexual-assaults/?_x_tr_sl=en&_x_tr_tl=id&_x_tr_hl=id&_x_tr_pto=tc Dianti, T. (2021). Regulasi Dinilai Tak Cukup Redam Kekerasan Seksual di Kampus. Diakses dari laman: https://www.dw.com/id/kekerasan-seksual-di-kampus/a-59838953 LM Psikologi. (2022). Kekerasan Seksual di Kampus. Diakses dari laman: https://lm.psikologi.ugm.ac.id/2022/05/kekerasan-seksual-di-kampus/ Putri, W. F. I. (2021). Kekerasan Seksual di Kampus Bagai Fenomena Gunung Es. Diakses dari laman: https://www.medcom.id/nasional/peristiwa/RkjWxeRK-kekerasan-seksual-di-kampus-bagai-fenomena-gunung-es